Kepemimpinan Pendidikan Islam di Banten: Komparasi Gerakan Pembaharuan Pendidikan Islam K.H. Mas Abdurrahman dan K.H. Syam’un - Badri, Muhammad Shofwan Mawally Nafis; Muslihah, Eneng; Shobri, Shobri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to understand the development and impact of the Islamic education reform movement in the Banten region during the Dutch colonial period. It uses qualitative literature research methods to identify, analyze, and compare the roles of K.H. Mas Abdurrahman and K.H. Syam'un in this movement. The research describes the history of the Islamic education reform movement in Banten and focuses on the comparison of educational leadership between K.H. Mas Abdurrahman and K.H. Syam'un. Additionally, it provides deep insights into their roles in this movement and its impact on further understanding of Islamic education reform and leadership in the Islamic Education Reform Movement in Banten.